Time : From Concept to Narrative Construct. - Meister, Jan Christoph (De Gruyter, 2011)
The anthology presents a selection of articles on the subject of "time". Among these are a number of German-language contributions presented in English translation for the first time ever, including seminal articles by Günter Müller, Eberhard Lämmert and Käte Hamburger. The authors address their shared topic from three major disciplinary angles: philosophy, narrative theory and cognitivist studies. As our experience of time is intrinsically linked to our ability to recount and narrate events, the productive design and receptive re-construction of time constructs plays a particularly important.